2020
DOI: 10.1039/c9sc06240h
|View full text |Cite
|
Sign up to set email alerts
|

Spectral deep learning for prediction and prospective validation of functional groups

Abstract: A new multi-label deep neural network architecture is used to combine Infrared and mass spectra, trained on single compounds to predict functional groups, and experimentally validated on complex mixtures.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 49 publications
3
110
0
Order By: Relevance
“…Recently, the combined input of FTIR and MS spectra was used to train a deep learning model to recognize the presence of functional groups such as carboxylic acid, aromaticity, and the ester group. 116 The authors concluded that FTIR spectra could in many cases reliably annotate such functional groups, but MS did offer additional information in a fair number of cases. In another recent example, infrared ion spectroscopy linked to mass spectrometry could readily separate enantiomeric N -acetylhexosamines identified in body fluid samples.…”
Section: Other Analytical Methodsmentioning
confidence: 99%
“…Recently, the combined input of FTIR and MS spectra was used to train a deep learning model to recognize the presence of functional groups such as carboxylic acid, aromaticity, and the ester group. 116 The authors concluded that FTIR spectra could in many cases reliably annotate such functional groups, but MS did offer additional information in a fair number of cases. In another recent example, infrared ion spectroscopy linked to mass spectrometry could readily separate enantiomeric N -acetylhexosamines identified in body fluid samples.…”
Section: Other Analytical Methodsmentioning
confidence: 99%
“…(They are not the only choices, and the research literature provides other alternatives, such as support vector machines and neural networks, that may be more appropriate vibrational spectral analysis. 12,13 ) The student handout and supporting information provide brief discussions of the assumptions of each of these models. The multiclass classification performed in Part III of this activity is structured as multiple one-vs-all binary 4 classifications, in which the probability of membership in each class is separately determined for each molecule and the class with the highest probability is then taken as the final predicted label.…”
Section: Four Common ML Classification Algorithms Are Implemented In This Exercise: Decisionmentioning
confidence: 99%
“…9 More specifically, ML has been applied to both infrared (IR) absorption and Raman vibrational spectroscopy, 10,11 including functional group identification. [12][13][14][15] Although the chemical education community acknowledges the need for student training in computational methods and ML, 16 there are limited pedagogical materials and no standard way of incorporating this into the curriculum. One approach has been the development of dedicated semester-long courses in scientific computing for chemists 17 or cheminformatics 18 that introduce programming in general and include modules on ML methods.…”
mentioning
confidence: 99%
“…An autonomous robotic experimentation platform requires both in situ and algorithmically quantifiable measurements. While efforts have gone into AI-based pattern recognition methods for advanced automated spectral analytics, [196,197] the more manageable output parameters may be derived from absorption-first excitonic peak, absorption peak line-width, concentration-and photoluminescence-peak emission energy, emission linewidth, quantum yield-spectroscopy on QDs.…”
Section: Aidriven Accelerated Materials Discovery and Optimizationmentioning
confidence: 99%